Desain kitchen set 5 jutaan / Woro Anjokrowati S., Tri Wahyu Handayani ; editor Lutfi Kurniawan. - WORO ANJOKROWATI S.; Tri Wahyu Handayani; Lutfi Kurniawan (Griya Kreasi, 2014)
151 hlm. : ilus. ; 22 cm [3 eks.]